2022
DOI: 10.3390/jcm11020305
|View full text |Cite
|
Sign up to set email alerts
|

Increased Natural Killer Cells Are Associated with Alcohol Liver Fibrosis and with T Cell and Cytotoxic Subpopulations Change

Abstract: Natural killer (NK) cells play a therapeutic role in liver fibrosis (LF). We aimed to analyze NK cells in heavy drinkers without cirrhosis or decompensated liver disease and establish correlations with other related subpopulations. Data on sociodemographic characteristics, alcohol consumption, laboratory parameters, and immunophenotyping of NK (CD16+/CD56+), T (CD3+), B (CD19+), NKT (CD16+/CD56+/CD3+), and cytotoxic (CD3-CD8+) cells were collected. Fibrosis-4 (FIB-4) scores were used to compare patients withou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 41 publications
2
5
0
Order By: Relevance
“…Zhang et al (2017) further confirmed that IL-17A inhibits hepatocyte autophagy through the IL-10/STAT3 signaling Frontiers in Molecular Biosciences frontiersin.org pathway and plays a pivotal role in the pathogenesis of LF. Moreover, natural killer, natural killer T, memory B, and central memory CD4 T cells have been demonstrated to be involved in the occurrence and development of LF (Wang and Yin, 2015;Huang et al, 2020;Zuluaga et al, 2020;Zuluaga et al, 2022). Therefore, our results were consistent with these previous reports, and our bioinformatics analysis further emphasized the important role of these immune cells in the pathogenesis of LF.…”
Section: Discussionsupporting
confidence: 92%
“…Zhang et al (2017) further confirmed that IL-17A inhibits hepatocyte autophagy through the IL-10/STAT3 signaling Frontiers in Molecular Biosciences frontiersin.org pathway and plays a pivotal role in the pathogenesis of LF. Moreover, natural killer, natural killer T, memory B, and central memory CD4 T cells have been demonstrated to be involved in the occurrence and development of LF (Wang and Yin, 2015;Huang et al, 2020;Zuluaga et al, 2020;Zuluaga et al, 2022). Therefore, our results were consistent with these previous reports, and our bioinformatics analysis further emphasized the important role of these immune cells in the pathogenesis of LF.…”
Section: Discussionsupporting
confidence: 92%
“…The results of this study suggest that AUD patients with advanced liver fibrosis have more cytotoxic CD56 + CD16 + NK cells, fewer cytokine-secreting CD56 + CD16 − NK cells and an increased lymphocyte activation, defined by HLA-DR expression, than patients without advanced liver fibrosis. Our group previously described the increase in the absolute counts of NK cells and cytotoxic T cells subsets in patients with advanced fibrosis, but these results expand the description of the phenotype of NK [ 26 ].…”
Section: Discussionsupporting
confidence: 62%
“…Considering that NK cells constitute the dominant lymphocyte population in the liver and that alcohol can suppress these NK cells 55 , we conducted an experiment to determine the changes in NK cells caused by probiotic strains in ALD. There were no significant differences in NK cell frequency or cytotoxicity in mice with ethanol-induced liver disease.…”
Section: Discussionmentioning
confidence: 99%